POLA, TATAHAN DAN SUNGGINGAN BONEKA WAYANG KULIT DAGELAN GAYA SURAKARTA DAN YOGYAKARTA SERTA KREASI PENGEMBANGANNYA - Ahmadi, Agus (Institut Seni Indoensia Surakarta, 2015)
The choice of clown (painting) puppet as the object of research is because of its simple and funny shape. This simple shape of puppet is very appropriate for a reference in making the pattern, inlaying and painting of the leather puppet for the beginner. Clown leather puppet /panakawanis a typical thing in Indonesia and it cannot be found in Indian where the original story comes from. The objectives of research are: to classify and to elaborate the inlay pattern/shape, size and motive applied to the clown puppet group; to explain the process and result of painting applied to Surakarta and Yogyakarta styles of clown puppet; as well as to express the clown puppet development creation. The research method used in this current study is a qualitative research method so that the research process is conducted in cycle, with repeatedly, ongoing or sustainable data collection activity. The result of research shows that the clown puppet group could be divided into 5 types consisting of 13 puppet characters in which each character of clown puppet is given puppet pattern example, inlay motiveshapes, and painting manifestation, in both Surakarta and Yogyakarta styles. The pattern and in lay of clown leather puppet group is much different from that of other leather puppet group. The difference is that the pattern and inlay of clown leather puppet group are simpler than that of jangkahan or bokongan puppet group. The unity of inlay and painting has been seen clearly in the painting inlay shape that becomes an overlapping decoration.Inlay is the border of painting motive and painting is the filler/color of inlay motive.Keywords: clown, leather puppet, creation.